2007
DOI: 10.1038/sj.bjp.0706998
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms underlying the pharmacological induction of phosphenes

Abstract: Visual sensations evoked by stimuli other than luminance changes are called phosphenes. Phosphenes may be an early symptom in a variety of diseases of the retina or of the visual pathways, but healthy individuals may perceive them as well. Phosphene‐like phenomena are perhaps the most common side effect reported in clinical pharmacology. Ivabradine, a novel anti‐anginal drug that reduces heart‐rate by inhibiting the hyperpolarization activated current expressed in cardiac sinoatrial node cells (If) induces pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 100 publications
0
45
0
7
Order By: Relevance
“…Phosphene-like phenomena are the common side effects of fever (high temperature) (Cervetto et al, 2007). Considering the mentioned findings, it supports that fever induces an elevated glutamate production that activates NMDARs.…”
Section: Phosphenes Due To Excess Upe Caused By Increased Ros Productmentioning
confidence: 62%
See 2 more Smart Citations
“…Phosphene-like phenomena are the common side effects of fever (high temperature) (Cervetto et al, 2007). Considering the mentioned findings, it supports that fever induces an elevated glutamate production that activates NMDARs.…”
Section: Phosphenes Due To Excess Upe Caused By Increased Ros Productmentioning
confidence: 62%
“…Another peak is at 703 nm (Khan and Kasha, 1970) and approximately 1270 nm (Baker and Kanofsky, 1991 In addition, as mentioned, glutamate has a significant function in thermoregulation by means of the NMDA ionotropic receptors (Yoshimatsu et al, 1993;Paro et al, 2003), and there is a significant association between temperature and glutamate excitotoxicity (Campos et al, 2012). Thus, glutamate-related phosphene induction through UPE may also be a possible mechanism relating fever (high body temperature) and phosphenes (Cervetto et al, 2007).…”
Section: Glutamate Triggered Upe and Phosphenesmentioning
confidence: 99%
See 1 more Smart Citation
“…A major obstacle of most existing agents is that they are not specific enough for sinoatrial (mainly HCN4-mediated) I h , but also block neuronal I h in several regions of the nervous system. For example, visual disturbances that result from block of retinal I h have been reported for several of these drugs (78). Moreover, some of the blockers may also interact with other ion channels.…”
Section: A Heart Rate-reducing Agentsmentioning
confidence: 99%
“…Cross-reactivity with I h channels Hyperpolarization voltage-gated channels are not exclusive to pacemaker cells in the sinoatrial node but are also found in neuronal I h channel retinal and CNS tissues [Cervetto et al 2007]. Because of the lipophobic nature of the structure of ivabradine it does not cross the bloodbrain barrier.…”
Section: Bradycardiamentioning
confidence: 99%